FOOD SECURITY OF CHERNIHIV REGION: ESSENCE, STRUCTURE, ASSESSMENT - STADNIK, Viktoriya; DVORNYK, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The essence of the concept of «food security» is studied. Theoretical and practical approaches to ensuring food security are studied. The general situation of food security of Ukraine is considered, the structure and features of its provision are determined. The general state and main aspects of the problems of food security of the Chernihiv region are disclosed and the main directions of its formation are determined. The main orientation of the regional organization of production and improvement of the living standard of the population is proposed, taking into account economic, socio-demographic and natural-climatic factors. It is determined that the theoretical features and regional structure of the agricultural sector of both Ukraine as a whole and Chernihiv region continue to be formed under the influence of the economic situation in the country. A diagnostic assessment of food security in the Chernihiv region was carried out. An analysis of the indicators of sufficiency of consumption of products of different groups in 2023 in the Chernihiv region is carried out. In particular, attention is paid to the main indicators that indicate the level of food security in the region. Scientific approaches to the development of a mechanism for ensuring food security by supporting domestic production have been expanded, namely, the introduction and support of organic production. According to statistics, in 2022, the area of land certified as organic or in transition in our region amounted to 3045.8 hectares, which is 12% less than in 2021 (0.22% of all arable land in the region). Producers of organic products grew 2502.7 tons of grain crops, including rye, oats, tritical, mustard, barley, buckwheat, etc. It is proved that organic production is one of the main directions of development of food security in the Chernihiv region. In particular, the priority strategy for sustainable development of the Chernihiv region for the period up to 2027 is the development of organic farming and the production of environmentally friendly food, one of the directions is the start of specialization of the Chernihiv region.
Keywords: food security; security; region; regional structure; economic security; agricultural production; agro-industrial complex; agri-food production; organic production; environmentally friendly products; strategic development